2017
DOI: 10.18632/oncotarget.16317
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Bmi1 in breast cancer stem cells suppresses tumor growth and proliferation

Abstract: Targeting cancer stem cells during initial treatment is important to reduce incidence of recurrent disease. Bmi1 has been associated with cancer stem cell self-renewal and aggressive disease. The purpose of this study was to determine the effects of downregulation of Bmi1 in breast cancer stem cells in order to target and eliminate the stem cell population in the tumor mass. Bmi1 was downregulated using two approaches in the mouse breast cancer stem cell line FMMC 419II—a small molecule inhibitor (PTC 209) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 45 publications
7
39
0
Order By: Relevance
“…Mechanistically, CUL4B promotes BMI1 expression and upregulates BMI1 via epigenetically repressing miR200b/c. BMI1, a member of the PcG protein, has been shown to play an important role in epigenetic regulation of cell differentiation and proliferation, as well as in the self‐renewal of CSCs . So far, multiple studies have demonstrated an oncogenic role of BMI1 in PCa progression .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, CUL4B promotes BMI1 expression and upregulates BMI1 via epigenetically repressing miR200b/c. BMI1, a member of the PcG protein, has been shown to play an important role in epigenetic regulation of cell differentiation and proliferation, as well as in the self‐renewal of CSCs . So far, multiple studies have demonstrated an oncogenic role of BMI1 in PCa progression .…”
Section: Discussionmentioning
confidence: 99%
“…BMI1, a member of the PcG protein, has been shown to play an important role in epigenetic regulation of cell differentiation and proliferation, as well as in the self-renewal of CSCs. 41 So far, multiple studies have demonstrated an oncogenic role of BMI1 in PCa progression. 14,42 BMI1 expression level was associated with invasion, metastasis, drug resistance, and poor prognosis of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Looking at the expression of CD49f as an established surface marker of breast cancer CSC, in vitro and in vivo experiments demonstrated that the CD49f-positive subpopulation of breast cancer cells was reduced after PTC-209 incubation. Additionally, PTC-209 markedly reduced size and weight of tumors in vivo [9].…”
Section: Introductionmentioning
confidence: 92%
“…In the initial study regarding PTC-209 by Kreso and coworkers, the authors described a profound effect of PTC-209 on the CSC fraction of colorectal cancer [5]. Since then, various studies investigated the role of BMI1 and/or the effect of BMI1 inhibition on the CSC and demonstrated a connection in glioma, hepatocellular carcinoma, and breast cancer [9,13,14]. Albeit rarely investigated, the current literature suggests a contribution of CSCs also for BTC [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation